2012
DOI: 10.4084/mjhid.2012.058
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients With Thalassemia Major and Intermedia in Kerman-Iran (I.R.)

Abstract: Thalassemia is the most common hemoglobin disorder in the world and thalassemia major and intermedia stand among the most severe forms. Due to recent improvements in treatment, patients with thalassemia have longer life expectancies; hence it is of utmost importance to pay careful attention to their quality of life together with life expectancy. This study was conducted to assess the quality of life in patients with thalassemia and also to compare it between thalassemia major and intermedia. In this cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 9 publications
5
17
3
1
Order By: Relevance
“…These findings revealed that patients and their families can adapt to the disease burden and can live a near normal life as others; they go to school and perform their homework, play with peers and go to tourism. This result is inconsistent with the study of Safizadeh and Farahmandinia [26] which revealed that the lowest score by their participants was for the school domain.…”
Section: Environmental Healthcontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings revealed that patients and their families can adapt to the disease burden and can live a near normal life as others; they go to school and perform their homework, play with peers and go to tourism. This result is inconsistent with the study of Safizadeh and Farahmandinia [26] which revealed that the lowest score by their participants was for the school domain.…”
Section: Environmental Healthcontrasting
confidence: 99%
“…These results are consistent with the results of [26,27] which revealed that the physical function had the lowest scores among all dimensions of their studies. Furthermore; other studies revealed that health-related QOL among patients with major/intermediate beta thalassemia is associated with poor physical health [28].…”
Section: Physical Health Consistentsupporting
confidence: 93%
See 1 more Smart Citation
“…3,8,[16][17][18][19][20] This study is the first to investigate and compare QoL in patients receiving blood transfusion and bone morrow transplantation. Iran is one of the pioneers in using BMT for β-thalassemia patients, 25 and thus this study can be remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 One of the most important issues in economic evaluation is measuring and evaluating different aspects of a patient's HRQoL. 15 Since all studies on HRQoL in β-thalassemia patients of Iran have focused on those who use blood transfusion, 3,8,[16][17][18][19][20] we decided to compare HRQoL in patients that use blood transfusion plus iron chelation (BTIC) therapy and those who have had bone marrow transplantation (BMT) using 2 different multiattribute quality of life (QoL) scales. In addition, we tried to assess the effects of different socio-economic characteristics on HRQoL.…”
mentioning
confidence: 99%